Reformasi Dinas Kependudukan dan Catatan Sipil dalam Perspektif New Public Service: Studi Kasus Sistem Informasi Administrasi Kependudukan (SIAK) - Taftahzani, Rezlan Izhar; Rafif, Faiz Akmal; Adya, Fabian Nathaniel Putra; Rosadi, Zidni Alfiyan; Indrawan, Jerry (Jurnal Ilmiah Wahana Pendidikan, 2025)
Public services in Indonesia's population administration and civil registry (Dukcapil) sector have been known to be complicated, slow, and prone to illegal levies, causing public dissatisfaction. Dukcapil reform is an urgent need to improve the quality of services and strengthen the legitimacy of the government. This study aims to analyze the implementation of the New Public Service (NPS) paradigm in Dukcapil reform, focusing on the translation of NPS principles in policies, success determinants, and recommendations for strengthening services. The research method uses literature studies and policy analysis. The results demonstrate that the implementation of New Public Service (NPS) principles, which prioritize involvement, openness, and the public interest, is reflected in public service reforms in the population administration sector, including Civil Registration Information System (SIAK), ball pick-up services, and e-KTP digitization. Even though these reforms increase the legitimacy and effectiveness of the administration, they nevertheless run into issues like infrastructure constraints and bureaucratic opposition. Strong leadership, political backing, and a shift in bureaucratic culture toward democratic ideals are necessary for consistent execution.